Indigenous land demarcation, traditional knowledge, and biodiversity in Brazil - Douglas Oliveira Diniz Gonçalves; Fran Espinoza; Dimas Pereira Duarte Júnior (Revista de Direito Econômico e Socioambiental)
Since the colonization of Brazil, both indigenous peoples and the nature are exploited, destroyed and appropriated for the sake of an economic model based on the accumulation of natural resources and products. Now faced with an environmental crisis, these destroyed worlds and diminished peoples and its practices emerge as potential sources for the protection and recovery of nature and biodiversity. Following this premise, the objective of the present study is to verify the potential role of indigenous lands demarcation on the protection of biodiversity in Brazil. The hypothesis planted is that the realization of indigenous peoples' land right can provide both conservation and recovery of biodiversity. In this study, the qualitative method was applied by assuming an interdisciplinary approach, with emphasis on law and sociology. Thus, it is concluded that the land right, when actually granted through the demarcation of Indigenous Lands, influences the conservation of biodiversity both directly and indirectly.